Creación de un software educativo para la asignatura de Electrótecnia para el primero de bachillerato técnico de la unidad educativa Fiscomisional “San José de Calasanz”, periodo 2014 –2015, de la parroquia y cantón Saraguro de la provincia de Loja - Ordóñez Chalán, Eugenio Vicente (2015)
The research is entitled CREATING AN EDUCATIONAL SOFTWARE FOR THE SUBJECT OF ELECTRICAL TECHNICIAN FOR FIRST BACHELOR OF EDUCATIONAL UNIT Fiscomisional" Calasanz "period 2014 - 2015, PARISH AND CANTON PROVINCE SARAGURO LOJA. In the educational context in which this research is carried out for lack of use and application of technological tools and / or digital teaching resources that strengthen and innovate the teaching-learning process is denoted, which is in contradiction with the demands of the current educational reform where it is claimed the use of ICT in education. The main objective of this paper is to introduce the use of educational software in the teaching-learning process, which allows teachers to be in accordance with the provisions of the curriculum reform of Ecuador expressing the need for the use of Information Technology and communication in the educational process. The research process is developed through deductive, inductive, descriptive statistical method that allowed the understanding of the problem, description of solutions and guidelines for educational software development, data analysis and interpretation, and report writing thesis, respectively. As you have used techniques to survey and classroom observation. The technical methodology used for the creation of educational software was sequentially comprising the steps of analysis software requirements, design, coding, testing and implementation. The results show that the teaching process reaches a good level of development but that no use of digital educational resources are made, wasting the average level of knowledge possessed by students in the use of the computer. The subjects in the educational software implemented for the block 3 and 5 were identified as the most complex, for which of multimedia content and activities developed performing the duty to motivate, inform and educate. Educational software created was implemented and socialized at the school. This new educational resource will make the educational process more participatory space and generating interest in the contents of the class.